Detection of Epistasis and Genetic Parameters of Some Quantitative Traits Through Triple Test Cross Analysis in Chickpea (Cicer Arietinum L.) (Bangladesh Journal of Botany, 2021)
Triple test cross analysis was carried out to detect the epistasis of thirteen yield and yield components in five chickpea (Cicer arietinum L.) crosses. Total epistatic effect was found to be non-significant for all the studied traits. Partitioning of total epistasis indicated the involvement of ‘i’ type (additive × additive) epistasis for DFF, PHFF, PWH, NPd/P, PdW/P, NS/P and SW/P in cross-1; NPBFF and NSBFF in cross-3 and for PHFF, DMF, PHMF and NSBMF in cross-5. The magnitude of additive component (D) was higher than that of the dominance component (H). Partial degree of dominance (√H/D) was observed for most of the traits. Both broad (h2b) and narrow (h2n) sense heritability were found to be moderately high. Positive and significant correlation between sums and differences indicated the direction of dominance towards decreasing parents and vice-versa.Bangladesh J. Bot. 50(2): 351-358, 2021 (June)